STUDI KEADILAN KEORGANISASIAN SEBAGAI PREDIKTOR DARI KOMITMEN ORGANISASI DENGAN MEDIASI KEPUASAN KERJA PADA PEGAWAI DINAS PENDIDIKAN, PEMUDA, DAN OLAHRAGA KABUPATEN GUNUNGKIDUL - Dheka Hudha Widya Permana (Riset Manajemen dan Akuntansi, 2021)
The purpose of this study was to examine the study of Organizational Justice as a Predictor of Organizational Commitment by Mediating Job Satisfaction. The method used is nonprobability sampling with the sampling technique using saturated sampling technique. The sample in this study were 210 respondents. The data analysis method used is Multiple Linear Regression using SPSS version 17. The results showed (1) there is a positive and significant influence of Distributive Justice on Job Satisfaction (2) there is a positive and significant effect of Procedural Justice on Job Satisfaction (3) there is a positive and significant influence on Job Satisfaction on Organizational Commitment (4) there is no positive influence and Distributive Justice is significant towards Organizational Commitment (5) there is no positive and significant influence Procedural Justice on Organizational Commitment.